Efektivitas Latihan Abdominal Stretching terhadap Penurunan Dismenorhe Remaja - Rika Handayani; Isnaeni Isnaeni; Ekayanti Hafidah Ahmad; Sanghati Sangahti; Yantimala Mahmud (Politeknik Kesehatan Kemenkes Mamuju, 2022)
Dysmenorrhea is a reproductive health problems that is always felt by some young women during menstruation. Lack of physical activity such as exercise, prolonged stress, consumption of nutritious foods, especially vegetables, is one of the triggers for dysmenorrhea. One non-pharmacological management that is safe to do to reduce dysmenorrhea pain is abdominal stretching exercises. This study aims to analyze the effectiveness of abdominal stretching exercises to reduce adolescent dysmenorrhea. This type of research is a quantitative study with a quasi-experimental design using a one group pretest posttest approach. The population in this study were all female students at the Wahdah Islamiyah Islamic Senior High School Makassar. The sample is 15 respondents was obtained using a purposive sampling technique. Respondents performed the abdominal stretching technique for 15 minutes every time they felt menstrual pain. The results showed that before being given abdominal stretching exercises an average value of 4.2000 was obtained with a standard deviation of 1.08233. Meanwhile, after being given abdominal stretching the average value was 2.4667 with a standard deviation of 1.06010. The results of the analysis of the paired sample t test obtained a value of 0.000 which means the value of < (0.05). It can be concluded that there is an effect of abdominal stretching on decreasing adolescent dysmenorrhea. Therefore, it is highly recommended for adolescents to do abdominal stretching exercises when experiencing dysmenorrhea.